Employee Engagement Implementation for Prevent Employee Turnover in Transportation Company - Desty Febrian, Wenny; Subagio, Mochammad; Suhendra, Agus; Syahridhan, Sayed; Soekirman, Atong (Greenation International Journal of Law and Social Sciences, 2024)
The purpose of this literature research is expected to build hypotheses regarding the influence between variables which can later be used for further research in the scope of human resource management. The literature review research article on the implementation of employee engagement to prevent employee turnover is a scientific literature article within the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from secondary data or previous research that is relevant to this research and comes from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Organizational Commitment affects Employee Engagement; 2) Organizational Culture affects Employee Engagement; 3) Career Path affects Employee Engagement; 4) Compensation affects Employee Engagement; 5) Organizational Commitment affects Employee Turnover; 6) Organizational Culture affects Employee Turnover; 7) Career Path affects Employee Turnover; and 8) Compensation affects Employee Turnover; and 9) Employee Engagement affects Employee Turnover.   Keywords: Employee Turnover, Employee Engagement, Organizational Commitment, Organizational Culture, Career Path, Compensation